Development of E-Modules Based on Inquiry-Based Learning to Support Junior High School Students’ Creative Thinking Skills on Flat-Side Space Structure Material - Monica Angelina Naibaho; Rohati Rohati; Sri Winarni (Journal of General Education and Humanities, 2025)
This study aims to develop an e-module based on Inquiry-Based Learning (IBL) to enhance junior high school students' creative thinking skills, particularly on flat-sided geometric shapes. The research was motivated by the low level of student creativity in mathematics, often attributed to conventional, teacher-centred learning methods. The research employed a Research and Development (R&D) approach, utilising the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants were eighth-grade students from SMP Negeri 16 Kota Jambi. The developed e-module was validated for practicality and effectiveness. The effectiveness was assessed through a pretest-posttest design, demonstrating a significant improvement in students’ creative thinking abilities across four key indicators: fluency, flexibility, originality, and elaboration. The average N-gain score of 0.79 indicates a high category of effectiveness. These findings suggest that integrating IBL with digital learning media provides an effective instructional tool for fostering students’ mathematical creativity. Therefore, the IBL-based e-module is recommended as an innovative alternative to support student-centred learning and the development of higher-order thinking skills in mathematics.